Inappropriate laboratory testing in internal medicine inpatients: Prevalence, causes and interventions. (March 2020) - Vrijsen, B.E.L.; Naaktgeboren, C.A.; Vos, L.M.; van Solinge, W.W.; Kaasjager, H.A.H.; ten Berg, M.J.
Abstract: Background: To reduce overutilization of laboratory testing many interventions have been tried, but selecting the most effective intervention for a given setting is challenging. To be sustainable, interventions need to align with healthcare providers' needs and daily practices. This study aimed to assess the extent of overutilization and the perspectives of healthcare providers, which may be used to guide the choice of intervention. Methods: The extent of inappropriate laboratory testing in internal medicine inpatients was evaluated using a database. Surveys and focus groups were used to investigate healthcare providers' perceptions on its causes and solutions. Results: On average, patients had 5.7 laboratory orders done during the first week of admission, whereas guidelines advise performing laboratory testing no more than twice per week. Repeat testing of normal test results occurred in up to 85% of patients. The frequency of laboratory testing was underestimated by survey responders, even though the majority of responders (78%) thought that laboratory tests are ordered too frequently. Residents were considered to be most responsible for laboratory test ordering. The primary causes of overutilization discussed were personal factors, such as a lack of awareness and knowledge, as well as feelings of insecurity. Regarding possible solutions, residents generally recommended educational interventions, whereas specialists tended to favour technical solutions such as lockouts. Conclusion: Inappropriate laboratory testing is common in internal medicine. The most important causes are a lack of awareness and knowledge, especially in residents. The intervention most favoured by residents is education, suggesting educational interventions may be most applicable. Highlights: In internal medicine inpatients, laboratory testing occurs on average 5.7 times per week, more than guidelines recommend. 59% of C-reactive protein (CRP) repeat tests are performed within the recommended minimum testing interval. Health care providers underestimate the extent of overutilization of laboratory testing. The most important causes of overutilization are a lack of awareness and knowledge, and feelings of insecurity. Specialists and residents have different opinions on what the most effective intervention is to reduce overutilization.